Introducing new grass-legume mixtures for pasture improvement in agro-pastoral farming systems - Franca A.; Caredda S.; Dettori D.; Sanna F. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Several new annual legumes recently introduced in the Mediterranean market for pasture improvement were grown in mixture with grasses. Two new mixtures were formed to represent different levels of complexity (COMPLEX and SIMPLE) and were compared with a local mixture of oats and Italian ryegrass (AFC). The results collected in the two-year experiment did not show great differences regarding total dry matter production between the COMPLEX and SIMPLE mixtures. Many of the species included in the COMPLEX mixture did not perform adequately, showing a lack of persistence and adaptability to the soil conditions of the site. The experiment suggested that mixtures are important in pasture improvement, however preliminary studies on the ecology and adaptability of the species to the site are of paramount importance. Sowing simple mixtures of 4 or 5 species is probably the most cost-effective way for farmers to improve or establish a balanced mix pasture.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)